Inclusive Financial Management Reconstruction for Adaptive Disabled Batik SMEs: Experimental Study - Yudhanto, Wildan; Aziz, Ahmad Abdul; Elavandy, Ediet Leo; Saputro, Muhammad Reza Henry; Ariyani, Ariyani (Lembaga Teewan Journal Solutions, 2026)
This study aims to reconstruct the paradigm of inclusive financial management to enhance the adaptive capacity of disabled batik SMEs in Magelang City. Despite the growing emphasis on financial inclusion, existing frameworks often fail to accommodate the unique constraints faced by entrepreneurs with disabilities in traditional industries. This research employs an experimental design by integrating accessibility, behavioral finance, and adaptive capability approaches through structured interventions, including financial literacy training and inclusive financial tools. The findings reveal that the reconstructed model significantly improves financial decision-making, resilience, and business adaptability. Furthermore, this study aligns with key Sustainable Development Goals (SDGs), including SDG 1 (No Poverty), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 17 (Partnerships for the Goals). The integration of social support and digital finance strengthens sustainability among marginalized SMEs. This study offers both theoretical contributions by advancing inclusive finance paradigms and practical implications for policymakers in fostering equitable and sustainable economic development in emerging economies.